2005
DOI: 10.1097/01.mlg.0000161357.12826.33
|View full text |Cite
|
Sign up to set email alerts
|

Cricothyroid Approximation and Subluxation in 21 Male‐to‐Female Transsexuals

Abstract: Objectives:To evaluate the medium-term outcome of cricothyroid approximation and subluxation (CTAS) with postoperative speech therapy for pitch elevation in male-to-female transsexuals. Study Design: Retrospective study of male-tofemale transsexuals who underwent pitch-raising surgery between November 1996 and August 2001.Methods: Twenty-one male-to-female transsexuals opted for surgical feminization of their voices after inadequate improvements with speech therapy alone. Electrolaryngographic measurements wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 10 publications
2
39
0
5
Order By: Relevance
“…5,7 Sometimes, surgical procedures are used to achieve a higher fundamental frequency (F 0 ). These procedures include cricothyroid approximation, 8 anterior commissure advancement, and endolaryngeal shortening of the vocal folds. 9 However, although surgery can assist in raising the F 0 , it is not problem-free and seldom sufficient to create a totally female voice.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Sometimes, surgical procedures are used to achieve a higher fundamental frequency (F 0 ). These procedures include cricothyroid approximation, 8 anterior commissure advancement, and endolaryngeal shortening of the vocal folds. 9 However, although surgery can assist in raising the F 0 , it is not problem-free and seldom sufficient to create a totally female voice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these procedures, the systematic review showed that other studies using surgical intervention performed over the past 10 years to increase the f0 in transsexual women were not included in the meta‐analysis because they did not have a control group. The surgical procedures included cricothyroid approximation and subluxation, laser‐assisted voice adjustment, Wendler glottoplasty, anterior glottic web formation assisted by temporary injection augmentation, a combined technique of transmucosal anterior suturing and stiffening of the vocal folds through a longitudinal cordotomy incision using a CO2 laser, Wendler glottoplasty and voice therapy, and cricoid‐thyroid approximation …”
Section: Discussionmentioning
confidence: 99%
“…The tension and FF are highest in the early postoperative period, and then decrease over time because of temporal mechanical factors, such as stress relaxation. 5,8,17 Therefore, the late results are more important for evaluating the success of the surgery. To overcome the inefficiency of CTA for obtaining the desired feminine pitch, the maximum limits should be applied during surgery.…”
Section: Discussionmentioning
confidence: 99%